1992
DOI: 10.4038/vjs.v4i1.6079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Application of Nitrogen and Molybdenum on the Uptake of Nitrogen, Seed Yield and its Quality of Soybeans (<em>Glycine max</em> (L.) Merr.)

Abstract: Effects of foliar nutrition of soybeans (cv.PB-I) with nitrogen and molybdenum on the seed yield and its quality are reported. Nitrogen uptake was positively affected by the foliar application of nitrogen. Foliar applcation of 1% ammonium nitrate solution t30kgN/ha) during the early pod-fill period has significantly increased the seed yield and the % protein in seeds. This effect was further enhanced by incorporation of 0.05 % ammonium molybdate in the spray solution. Application of nitrogen: 3.0kgN/ha at two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Deficiency of this element causes a reduction of nodule dry weight . In this concern , Ranaweera (1992) reported that nitrogen and molybdenum application had a significant effect on increasing nitrogen percent and uptake at different growth stages as well as protein percentage and yield in soybean seeds . Also , Liu et al (2005) reported that molybdenum significantly prompted accumulation of root and a aboveground biomass of soybean .…”
Section: Effect Of Rhizobium Inoculation Under Bio-and Mineral Fertilmentioning
confidence: 99%
“…Deficiency of this element causes a reduction of nodule dry weight . In this concern , Ranaweera (1992) reported that nitrogen and molybdenum application had a significant effect on increasing nitrogen percent and uptake at different growth stages as well as protein percentage and yield in soybean seeds . Also , Liu et al (2005) reported that molybdenum significantly prompted accumulation of root and a aboveground biomass of soybean .…”
Section: Effect Of Rhizobium Inoculation Under Bio-and Mineral Fertilmentioning
confidence: 99%